Effects of streptokinase in patients presenting within 6 hours of prolonged chest pain with ST segment depression. - White, H. D. (1995)
BACKGROUND--The effects of streptokinase on the occurrence of a combined clinical outcome in patients presenting with recent chest pain and ST depression were investigated in view of the role of thrombus in the pathogenesis of acute ischaemic syndromes. METHODS--112 patients aged < or = 75 years presenting within 6 h of the last episode of ischaemic chest pain of least 20 min duration with > or = 1 mm ST depression were randomised in a double blind manner to receive either streptokinase 1.5 million units over 30 min (n = 57) or placebo (n = 55). The primary end point was the combination of death, frequency of myocardial infarction (defined as peak creatine kinase > 600 U/ml), need for angiography because of uncontrollable ischaemia, and an exercise test within 35 days showing > or = 1 mm ST depression at < or = 6 min. The secondary end points were safety, frequency of chest pain, readmission with myocardial infarction or unstable angina, or need for revascularisation between 35 days and 1 year. The severity of ST depression on presentation was analysed with respect to clinical outcome. RESULTS--The frequency of the combined hierarchical end point of death, myocardial infarction, early angiography, and a positive exercise test was 82% (47 of 57 patients) with streptokinase and 75% (41 of 55 patients) with placebo. There were four deaths, two in each group. 27 patients (47%) receiving streptokinase and 22 (40%) receiving placebo developed myocardial infarction. 11 patients (eight streptokinase and three placebo) required coronary arteriography and subsequent revascularisation because of angina uncontrolled by medical treatment. 44 patients (22 in each group) had a positive exercise test. There were three further cardiac deaths (one streptokinase, two placebo), and three noncardiac deaths within 1 year. A conservative approach to intervention was adopted and over a period of 1 year 29 patients (26%) (13 streptokinase and 16 placebo) underwent revascularisation procedures. Three patients (two streptokinase and one placebo) required transfusion. ST depression > or = 3 mm had 90% specificity but only 60% positive predictive value for myocardial infarction at presentation (P = 0.008, stepwise logistic regression). ST depression > or = 2 mm was predictive of death, late development of myocardial infarction, or a need for angiography (P = 0.02). CONCLUSION--Patients presenting with ischaemic chest pain and ST depression frequently develop myocardial infarction. Severe ST depression is predictive of an adverse outcome. The 35 day (3.6% cardiac and total) and 1 year mortality (8.9% total, 6.3% cardiac) are low with conservative management and expeditious revascularisation. Streptokinase treatment within 6 h of the last episode of pain does not seem to be beneficial.